Cover Feature: Towards Atomically Precise Supported Catalysts from Monolayer‐Protected Clusters: The Critical Role of the Support (Chem. Eur. J. 31/2020). Issue 31 (8th May 2020) - Longo, Alessandro; de Boed, Ewoud J. J.; Mammen, Nisha; van der Linden, Marte; Honkala, Karoliina; Häkkinen, Hannu; de Jongh, Petra E.; Donoeva, Baira
Abstract : The fate of phosphine‐protected gold clusters is shown to be determined by the surface acidity of the oxide support they are deposited on. Using X‐ray absorption spectroscopy and density functional theory computations, this work shows that, independent of the size of the cluster, on Brønsted acid supports, it completely disintegrates into gold‐phosphine complexes, whereas on Lewis acid supports, the ligands peel away leaving behind the metallic gold cluster. More information can be found in the Full Paper by A. Longo, H. Häkkinen, B. Donoeva, et al. on page 7051 .